2013
DOI: 10.1111/jocn.12449
|View full text |Cite
|
Sign up to set email alerts
|

SISRH’ – a new model to manage sexual health following a spinal cord injury: our experience

Abstract: The progressive model portrayed discrete phases of sexual health management, which collectively portray the whole. Team members identified a level of involvement to compliment their skills and knowledge. The audit demonstrated that the primary barriers to involvement were not culture, language or attitude as hypothesised, but inadequate knowledge, addressable through education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…These aspects are significantly emphasized in the booklet. (1,3,7,8,25) The booklet stresses the relevance of the participation of partners, when they exist, in the sexual rehabilitation, because their learning process before the new health condition may contribute to a more satisfactory sexual life for the couples. Both people with spinal cord injury and their partners must have the opportunity to address this topic unreservedly with healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These aspects are significantly emphasized in the booklet. (1,3,7,8,25) The booklet stresses the relevance of the participation of partners, when they exist, in the sexual rehabilitation, because their learning process before the new health condition may contribute to a more satisfactory sexual life for the couples. Both people with spinal cord injury and their partners must have the opportunity to address this topic unreservedly with healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to encourage the maintenance of the sexual identity to preserve the basic human needs, since the first hospital admission until the outpatient follow-up. (8) To achieve this goal, it is essential that people with spinal cord injury receive guidance on possible changes and adaptation methods, because information may effectively contribute to clarifying doubts and reducing fears regarding the new health condition. (1) There is a lack of educational materials oriented to the sexuality of people with spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…The people in this study who were sexually inactive prior to their SCI due to marital status, age or pre-existing illness suggested that education on sexual functioning was unnecessary. Such views would be consistent with a culture in Ireland of traditional values and religious beliefs on sexual activity outside marriage and between older people (Catholicscomehome.org, 2021; The General Synod of the Church of Ireland, 2016; Wallace, 2012) but are contrary to much existing literature that affirms that education on sexual functioning are of paramount importance to people with SCI and should be treated as a priority during rehabilitation (Abramson et al, 2007;Hartshorn et al, 2013). In our study, such views were offered by participants who were sexually active prior to their injury, validating that sexual functioning was important to them, and many actively sought information on sexual functioning.…”
Section: Discussionmentioning
confidence: 87%
“…Education on sexual functioning (such as genital arousal, ejaculation and orgasm) should be integral to the rehabilitation programme as maintaining a healthy sex life after SCI is important to many individuals (Hartshorn et al, 2013;Othman & Engkasan, 2011;Saif et al, 2013). SCI impacts the sexuality of men and women differently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation